The health of internally displaced children in sub-Saharan Africa: a scoping review (2020)
Background: Internally displaced children are those who have been forced to flee their homes due to severe unfavourable conditions (war, violence or disasters) but have not crossed international borders. Emerging research shows these children face multiple health challenges. However, we found no review focused solely on the health of such internally displaced children. Thus, this review sought to examine what is known about their health and their health concerns. Methods: A scoping review of the literature was conducted. A total of 10 databases were searched in January 2019, yielding 6602 articles after duplicates were eliminated. Two research assistants independently selected articles that met inclusion criteria. A numerical summary and thematic analysis were conducted to facilitate data extraction and data analysis. Results: A total of 25 articles met the inclusion criteria, including 16 quantitative, 6 qualitative and 3 mixed methods studies. The findings reveal elevated mental health problems and infectious diseases in this population. Findings on the nutritional status of internally displaced children as a broad group are mixed, with some studies showing poorer nutritional status among the children in this group and others showing poorer nutritional health status among host society children. Internally displaced children also experience challenges with access to health services. Premigration factors (trauma) and postmigration factors (humanitarian assistance on displacement) all contribute to the health of internally displaced children. Conclusion: Findings provide insight into the complex array of factors influencing the health of internally displaced children. More intervention studies are required to address the needs of this population.